Does Rapid Eye Movement Sleep Aggravate Obstructive Sleep Apnea? - Kim, Sung Hee (Clin Exp Otorhinolaryngol, 2019)
OBJECTIVES. To investigate the apnea-hypopnea index (AHI) according to the sleep stage in more detail after control of posture. METHODS. Patients who underwent nocturnal polysomnography between December 2007 and July 2018 were retrospectively evaluated. Inclusion criteria were as follows: age >18 years, sleep efficacy >80%, and patients who underwent polysomnography only in the supine position (100% of the time). Patients were classified into different groups according to the methods: the first, rapid eye movement (REM)-dominant group (AHI(REM)/AHI(NREM) >2), non-rapid eye movement (NREM)-dominant group (AHI(NREM)/AHI(REM) >2), and non-dominant group; and the second, light sleep group (AHI(N1N2)>AHI(SWS)) and slow wave sleep (SWS) group (AHI(SWS)>AHI(N1N2)). RESULTS. A total of 234 patients (mean age, 47.4±13.9 years) were included in the study. There were 108 patients (46.2%) in the REM-dominant group, 88 (37.6%) in the non-dominant group, and 38 (16.2%) in the NREM-dominant group. The AHI was significantly higher in the NREM-dominant group than in the REM-dominant group (32.9±22.9 events/hr vs. 18.3±9.5 events/hr, respectively). There were improvements in the AHI from stage 1 to SWS in NREM sleep with the highest level in REM sleep. A higher AHI(SWS) than AHI(N1N2) was found in 16 of 234 patients (6.8%); however, there were no significant predictors of these unexpected results except AHI. CONCLUSION. Our results demonstrated the highest AHI during REM sleep stage in total participants after control of posture. However, there were 16.2% of patients showed NREM-dominant pattern (AHI(NREM)/AHI(REM) >2) and 6.8% of patients showed higher AHI(SWS) than AHI(N1N2). Therefore, each group might have a different pathophysiology of obstructive sleep apnea (OSA), and we need to consider this point when we treat the patients with OSA.